2000
DOI: 10.1007/s002689910058
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hepatic Catabolic Stress Response in Patients with Cirrhosis and Chronic Hepatitis

Abstract: Open (OC) or laparoscopic (LC) cholecystectomy is considered a relative contraindication in patients with liver cirrhosis. The effect of LC and OC on the hepatic catabolic stress response was studied in patients with postnecrotic liver cirrhosis and chronic hepatitis to define the most suitable procedure from a metabolic point of view. Altogether 14 patients with cirrhosis and 14 with chronic hepatitis were randomized to LC or OC (n = 7 in each group). The increase in the functional hepatic nitrogen clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The result of their study showed an association of surgical severity and type of analgesic treatment on the level of corticosterone through surgery, but none of them have reached the objectives of this study. Lausten et al [ 6 ] demonstrated the result of open and laparoscopic cholecystectomy on hepatic stress response in patients with postnecrotic liver cirrhosis and chronic hepatitis. Besides other results, the changes of cortisol in both groups between pre- and postoperative time were not significant in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of their study showed an association of surgical severity and type of analgesic treatment on the level of corticosterone through surgery, but none of them have reached the objectives of this study. Lausten et al [ 6 ] demonstrated the result of open and laparoscopic cholecystectomy on hepatic stress response in patients with postnecrotic liver cirrhosis and chronic hepatitis. Besides other results, the changes of cortisol in both groups between pre- and postoperative time were not significant in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The data from these studies suggest a positive correlation between the degrees of adrenal dysfunction with severity of liver disease [ 13 , 21 ]. Furthermore, other studies have reported the increased level of corticosterone throughout surgery, anesthesia, and postoperative course, but yet no studies have been able to investigate the changes in the function of the HPA axis before and after surgery in cirrhotic patients [ 1 , 6 8 , 13 , 14 , 24 , 25 ]. As a result, this study was designed to evaluate the function of HPA axis in response to surgical stress in cirrhotic rats compared with noncirrhotics by measuring corticosterone and blood sugar levels before and after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery should be undertaken in cirrhotic patients with symptomatic gallstone disease at an optimal time; otherwise, there is a risk of functional decompensation of liver, which has dismal outcomes. Laparoscopic cholecystectomy should be the preferred option in cirrhotic patients because of advantages such as (1) minimally invasive procedure with less morbidity and quick recovery with high patients compliance [15], (2) better magnification of view, laparoscopy is helpful to observe minute vascular channels more clearly. Portal venous collaterals and congested gall bladder bed also handled properly to reduce hemorrhagic complications [16], (3) associated with less postoperative complications such as surgical site infections, incisional hernia, and post-operative pain [17].…”
Section: Discussionmentioning
confidence: 99%
“…For data management reasons, we listed both groups as separate trials. 46,47 All other trials used a two-arm parallel-group design.…”
Section: Patient Characteristics and Trial Designsmentioning
confidence: 99%